Skincare Product Purchase Intention: Brand Reputation, Information Quality, Availability of Products, and Perceived Behavioral Control - Jessica Claudia; Tommy Setiawan Ruslim (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
The skincare industry in Indonesia has experienced rapid growth, driven by increasing public awareness of skin health and evolving beauty standards, especially among younger consumers. Amid intense competition and the rise of local brands, understanding the factors that influence purchase intention is crucial for brand sustainability. This study investigates the influence of brand reputation, information quality, product availability, and perceived behavioral control on consumer purchase intention toward Somethinc, one of Indonesia’s leading local skincare brands. Employing a quantitative approach with a causal research design, data were collected from 185 respondents in Jakarta who had previously purchased and used Somethinc products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results show that brand reputation and product availability have a significant and positive impact on purchase intention, emphasizing the importance of brand trust and product accessibility. In contrast, information quality and perceived behavioral control did not show a significant effect, suggesting that emotional and brand-driven factors may outweigh technical or rational considerations in skincare purchases. These findings offer valuable insights for marketers to refine branding and distribution strategies in a highly competitive beauty market.